2021
DOI: 10.1016/j.ajhg.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of splicing variants in disease genes and the ability of RNA analysis to reduce uncertainty in clinical interpretation

Abstract: The complexities of gene expression pose challenges for the clinical interpretation of splicing variants. To better understand splicing variants and their contribution to hereditary disease, we evaluated their prevalence, clinical classifications, and associations with diseases, inheritance, and functional characteristics in a 689,321-person clinical cohort and two large public datasets. In the clinical cohort, splicing variants represented 13% of all variants classified as pathogenic (P), likely pathogenic (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…In principle, both coding and intronic variants within a gene have the potential to affect splicing (Cooper et al, 2009;Scotti and Swanson, 2016;Anna and Monika, 2018;Truty et al, 2021). Genetic variants occurring within the 5 splice site GT dinucleotide, whenever found in disease-causing or disease-predisposing genes, have generally been classified as pathogenic (Mount et al, 2019;Stenson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, both coding and intronic variants within a gene have the potential to affect splicing (Cooper et al, 2009;Scotti and Swanson, 2016;Anna and Monika, 2018;Truty et al, 2021). Genetic variants occurring within the 5 splice site GT dinucleotide, whenever found in disease-causing or disease-predisposing genes, have generally been classified as pathogenic (Mount et al, 2019;Stenson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study by Invitae aimed to exemplify the utility of RNA analysis for reclassifying splicing VUS (Truty et al, 2021). The investigators analyzed a significantly large sample consisting of nearly 700k patients from a clinical cohort plus individuals from two large public datasets (i.e.…”
Section: Hereditary Cancermentioning
confidence: 99%
“…The investigators analyzed a significantly large sample consisting of nearly 700k patients from a clinical cohort plus individuals from two large public datasets (i.e. ClinVar and Genome Aggregation Database/gnomAD ) (Truty et al, 2021). In their clinical cohort, Invitae found that 5.4% of individuals had at least one splicing VUS (most of which were identified outside of essential splice sites), and that splicing variants represented 13% of all variants classified as (likely) pathogenic or VUS.…”
Section: Hereditary Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While the accuracy of in silico algorithms in predicting whether a variant will cause mis-splicing has been comprehensively assessed [6][7][8][9] , there is currently no reliable means to predict which mis-splicing event(s) may occur in response to a variant that activates mis-splicing. As a result of this and other factors, the vast majority of splice site variants are classified as variants of uncertain significance (VUS); a non-actionable diagnostic endpoint in genomic medicine 10 .…”
Section: Introductionmentioning
confidence: 99%